Consider $u_t + uu_x + \alpha u = 0$ for $t > 0$, all $x$ where $\alpha > 0$ is a constant. Find the characteristic equations for the equation with initial data $u(x, 0) = f(x)$ given. Show that a shock cannot form if $\alpha \geq \max_{r \in H}|f'(r)|$ where $H = \{r : f'(r) < 0\}$ or if $H$ is empty.

So far, I've found the characteristics by parametrizing $$\begin {cases} x_s=u, x(0,r)=r \\ t_s=1,t(0,r)=0 \\ u_s = -\alpha u, u(0,r)=f(r)\end {cases}$$ Then $\frac{du}{ds}=-\alpha u \Rightarrow u = C_1 e^{-\alpha s}$. Considering the initial condition, $u = f(r)e^{-\alpha s}.$

$\frac{dt}{ds} = 1 \Rightarrow t = s$ (since $t(0,r)=0$)

$\frac{dx}{ds}=u=f(r)e^{-\alpha s} \Rightarrow x = -\frac{1}{\alpha}f(r)e^{-\alpha s}+\frac{1}{\alpha}f(r)+r$ (since $x(0,r)=r$), i.e. $x = -\frac{1}{\alpha}f(r)e^{-\alpha t}+\frac{1}{\alpha}f(r)+r$

So how do we show that a shock cannot form?

  • $\begingroup$ What do you know about shocks? When do they form? $\endgroup$ – Mattos Dec 6 '18 at 3:42

This (dissipative) Burgers' equation with relaxation is a typical example of conditional shock formation. The answer follows the steps in this post. The characteristics are the curves $$ x = -f(x_0)\frac{e^{-\alpha t} - 1}{\alpha} + x_0 $$ along which the solution satisfies $$ u = f\left(x - \frac{e^{\alpha t}-1}{\alpha} u\right)e^{-\alpha t} . $$ Computing $\frac{\text d x}{\text d x_0}$, we find that this derivative vanishes at a given positive time $t$ -i.e. a shock wave forms- if $$ -\frac{\ln(1+\alpha/f'(x_0))}{\alpha} = t >0 . $$ For this to be possible, the logarithm should be negative, and thus, $f'(x_0)<0$ (in other words, $x_0\in H$). However, if $-\alpha < f'(x_0) < 0$ for $x_0$ in $H$, the logarithm becomes complex and no shock occurs. Hence the conclusion: a shock cannot occur if $\max_{x_0 \in H}|f'(x_0)| \leq \alpha$ or if $H = \emptyset$. Alternatively, this condition may be written $\inf_{x_0 \in\Bbb R} f'(x_0) \geqslant -\alpha$.


Harry49 already answered to the question.

I am not standing up here to give another answer. My intervention is a comment, but too long to be edited in the comments section.

The analytical solving of the PDE with the specified boundary condition is especially interesting as shown below. $$u_t+uu_x=-\alpha u \tag 1$$ The Charpit-Lagrange equations are : $$\frac{dt}{1}=\frac{dx}{u}=\frac{du}{(-\alpha u)}$$ A first family of characteristic curves comes from $\frac{dx}{u}=\frac{du}{(-\alpha u)}$ : $$u+\alpha x =c_1$$ A second family of characteristic curves comes from $\frac{dt}{1}=\frac{du}{(-\alpha u)}$ : $$ue^{-\alpha t}=c_2$$ The general solution of the PDE Eq.$(1)$ expressed on the form of implicit equation is : $$u+\alpha x=\Phi\left(ue^{-\alpha t}\right) \tag 2$$ where $\Phi$ is an arbitrary function (to be determined according to boundary condition).

Condition : $u(x,0)=f(x)$ with $f(x)$ a known (given) function.

$$f(x)+\alpha x=\Phi\left(f(x)e^{0}\right)=\Phi\left(f(x)\right)$$ Let $X=f(x)$ and $x=f^{-1}(X)$

$f^{-1}$ denotes the inverse function of $f$. $$\Phi(X)=X+\alpha f^{-1}(X)$$ So, the function $\Phi$ is determined. We put it into Eq.$(2)$. $$u+\alpha x=ue^{-\alpha t}+\alpha f^{-1}\left(ue^{-\alpha t}\right)$$ $$f^{-1}\left(ue^{-\alpha t}\right)=x+\frac{u}{\alpha}\left(1-e^{-\alpha t}\right)$$ $$ue^{-\alpha t}=f\left(x+\frac{u}{\alpha}\left(1-e^{-\alpha t}\right)\right) \tag 3$$ Eq.$(3)$ is the implicite form of the analytic solution of $u_t+uu_x+\alpha u=0$ with condition $u(x,0)=f(x)$.

The explicite form of $u(x,t)$ requires to solve Eq.$(3)$ for $u$. The possibility to do it analytically depends on the kind of function $f$.

Of course, this is only for information without answering to the OP question as mentioned at first place.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.